Evaluation of the European Society of Urogenital Radiology (ESUR) PI-RADS scoring system for assessment of extra-prostatic extension in prostatic carcinoma. Issue 10 (October 2015) - Schieda, Nicola; Quon, Jeffrey S.; Lim, Christopher; El-Khodary, Mohammed; Shabana, Wael; Singh, Vivek; Morash, Christopher; Breau, Rodney H.; McInnes, Matthew D.F.; Flood, Trevor A.
Graphical abstract: Highlights: The PI-RADS criteria for EPE improves sensitivity without reducing specificity. The PI-RADS criteria for EPE improves overall accuracy compared to non-standardized reporting. The PI-RADS criteria for EPE reduces differences related to reader experience. The PI-RADS scoring system provides a scale of increasing specificity for EPE. Abstract: Introduction: To evaluate extra-prostatic extension (EPE) comparing PI-RADS to non-standardized reporting. Materials and methods: With IRB approval, 145 consecutive patients underwent radical prostatectomy (RP) and multi-parametric (T2W + DWI + DCE) MRI between 2012 and 2013. Eighty patients (66.3% with EPE) were staged without PI-RADS and 65 patients (64.6% with EPE) were staged using a 5-point PI-RADS scoring system. Studies were reported by fellowship-trained radiologists in routine clinical practice. Individual PIRADS scores were assessed using ROC to determine the score which optimized sensitivity/specificity. Diagnostic accuracy for EPE was compared with/without PI-RADS using the McNemar test. Subgroup analysis by radiologist experience was performed using Spearman correlation and chi-square. Results: Area under ROC curve for EPE using PI-RADS was 0.62 and optimal sensitivity/specificity was achieved with PI-RADS score ≥3. Compared to non-standardized reporting, sensitivity for EPE improved with PI-RADS (59.5% [49.1–68.2] vs. 24.5% [16.7–31.2]), p = 0.01; with no difference in specificity (68.0% [50.5–82.6]) vs. (75.0% [60.1–87.6]), p = 0.06. Overall accuracy improved with PI-RADS (62.7% [49.6–73.6] vs. 42.0% [31.7–50.7%]), p = 0.006. Diagnostic accuracy was better among experienced radiologists without PI-RADS ( p = 0.005); however, there was no difference in accuracy by reader experience using PI-RADS ( p = 0.24). Conclusion: The PI-RADS criteria for EPE improves sensitivity without reducing specificity. PI-RADS may reduce differences in accuracy by reader experience.